2023
DOI: 10.3389/fimmu.2023.1084448
|View full text |Cite
|
Sign up to set email alerts
|

T cells and their products in diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease and has gradually become a public health problem worldwide. DKD is increasingly recognized as a comprehensive inflammatory disease that is largely regulated by T cells. Given the pivotal role of T cells and T cells-producing cytokines in DKD, we summarized recent advances concerning T cells in the progression of type 2 diabetic nephropathy and provided a novel perspective of immune-related factors in diabetes. Specific emphasis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 196 publications
(252 reference statements)
1
7
0
Order By: Relevance
“…In our study, a high CONUT score was found to be associated with an increased risk of ESRD in patients with diabetic kidney disease, which is the most common complication in these patients. Research has suggested that immune inflammation and nutritional status may be closely related to the progression of renal function in diabetic kidney disease patients ( Zhang et al, 2022 ; Liu et al, 2023 ). Among the components of CONUT score, albumin serves as a cornerstone for nutritional assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, a high CONUT score was found to be associated with an increased risk of ESRD in patients with diabetic kidney disease, which is the most common complication in these patients. Research has suggested that immune inflammation and nutritional status may be closely related to the progression of renal function in diabetic kidney disease patients ( Zhang et al, 2022 ; Liu et al, 2023 ). Among the components of CONUT score, albumin serves as a cornerstone for nutritional assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Renin-angiotensin system (RAS) inhibitors, sodium-glucose cotransporter-2 inhibitors (SGLT-2is), glucagon-like peptide-1 receptor agonists (GLP-1RAs), and mineralocorticoid receptor antagonist (MRA) have been proven to effectively mitigate the impact of these risk factors on diabetic kidney disease patients ( Yang et al, 2022 ; Filippatos et al, 2023 ; Giglio et al, 2023 ). However, a growing body of research indicates that chronic inflammation, immune dysregulation, and nutritional status also play crucial roles in the progression of diabetic kidney disease ( Yang and Mou, 2017 ; Zhang et al, 2022 ; Liu et al, 2023 ; Zhang et al, 2023 ). As such, early identification and management of these non-traditional risk factors may be critical for optimizing the prognosis of diabetic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, T cells can directly induce tubular cell apoptosis and contribute to tubulointerstitial fibrosis [ 30 , 31 ]. In diabetic kidney disease, T cells also play a critical role in the pathogenesis of kidney disease [ 32 , 33 ]. T-cell infiltration in the glomerulus is associated with the development of albuminuria and renal fibrosis [ 16 , 34 ].…”
Section: Immunometabolic Alterations In Kidney Diseasementioning
confidence: 99%
“…[11] Research has demonstrated that the JAK/STAT signaling pathway is closely associated with the pathophysiological processes of kidney diseases. [12] Multiple studies have reported a significant correlation between JAK/STAT signaling and renal fibrosis. [13,14] The reports indicate that CXC chemokine receptor type 4 (CXCR4) activation leads to the activation of JAK2/STAT3 and JAK3/STAT6 signaling in renal cells, subsequently reducing the abundance of glycogen synthase kinase-3beta (GSK3β) mRNA and exacerbating CKD renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%